HUBUNGAN TINGKAT PARTISIPASI IBU MENGIKUTI POSYANDU DENGAN STATUS GIZI BALITA DI DESA MULUR RT 03/VI BENDOSARI SUKOHARJO - Ratna Indriati; Christin Lidyawati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2017)
Posyandu is a method to monitor growth child. The scope of children is an indicator ofpublic participation in posyandu.The percentage of the scope of children weighed inCentral Java in 2015 is 73.9 %, decrease compared to the 2014 80.4%. Posyanduactivities in the village Mulur is routinely performed every month, but some women notroutinely come, and still found children with a weight less. Purpose and benefit : to knowrelations participation mother follow posyandu with the status of nutrition child. Benefitsresearch is provide an illustration of the importance of follow posyandu activities as aneffort to increase the nutrition of child.The subject of study: 35 mother and child age 1 – 5 years in posyandu village MulurSukoharjo. Method: research of analytic observation, design correlation with the crosssectional. The sample of this study in total sampling.The data analysis by test chi squarewith p= 0.05.The result of research show mother to the level of active participation 13 people(37.14%), less active 10 people (28.57%) not active 12 people (34.29%).Children withnutrition good 23 children (65.71%) and malnutrition 12 children (34.29%).The results ofthe analysis use test chi square obtained p=0.039 (p < 0.05) which means Ha received.Conclusion: there was a correlation level of participation mother follow posyandu with thestatus nutrition of child.Keywords: Level of participation, posyandu activities, nutritional status of child